The Influence of Personnel Workload at the Control Area Unit to Service Quality of Air Traffic Center (ATC) in Jakarta - Imandoko, Hening Bramantyo; Rafli, Muhammad; Budiman, Cecep (Institut Transportasi dan Logistik Trisakti, 2022)
This study aims to investigate the influence of personnel workload at the ATC (Air Traffic Center) to service quality of ATC using quantitative approach. The data was collected using a questionnaire, to grasp the respondents’ perception. The population of this study are those who work in ATC, Jakarta, Indonesia. Purposive sampling technique is employed in this study. The number of the respondents of this study are 20 persons comprising, air traffic control staff and managers. The data was analyzed using SPSS. . The result shows that there is a significant influence on personnel workload at the control area unit to service quality of air traffic center in Jakarta, Indonesia.